Reliable power system operation plan - steady state contingency analysis - Rashid, Rina (2014)
To ensure that Sabah Grid transmission system is planned and operated safely, economically and reliably, steady state contingency analysis must be performed. This analysis is performed to ensure that the system meets all requirements and Grid Code standards under normal operations and given a variety of outages or contingencies and other operating condition, where applicable. Steady state contingency analysis is the study of the outage of elements such as transmission lines, transformers and generators, and investigation of the resulting effects on line power flows and bus voltages of the remaining system. This study is prepared with the intent to put forward issues and recommendations towards achieving a reliable power system operation plan. This will enable the day-to-day system operation in the Sabah Grid to meet system demand while maintaining the reliability of the grid system within acceptable standards by maximizing the use of available and existing generation and transmission resources for system operation. The task of steady state contingency analysis is to calculate power flows in outage states in which one or more system components are out of service. A transmission system must satisfy security criteria in both normal and outage states. This project presents the steady state contingency analysis for the period of year 2014 to year 2016. In this study, the contingency analysis will be performed using the power flow method and contingency analysis using Siemens PTI software Power System Power System Simulator for Engineering (PSS/E).